2022
DOI: 10.3390/foods11131991
|View full text |Cite
|
Sign up to set email alerts
|

Flaxseed Polysaccharide Alters Colonic Gene Expression of Lipid Metabolism and Energy Metabolism in Obese Rats

Abstract: Obesity is one of the most serious public health challenges. Recently, we found that flaxseed polysaccharides (FPs) had an anti-obesity effect through promoting lipid metabolism, but the obesity-inhibiting pathway of FP is still unclear. In this study, after FP intervention in an obese rat model, a transcriptome study was performed to further investigate how FP intervention alters the gene expression of colonic epithelial tissues (CETs). The results showed that there were 3785 genes differentially expressed du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The results showed that eight genes, including XLOC_003676, XLOC_011515, VAX1, Q07610, RIMBP2, OR5T1, XLOC_013038 and PTPN3, had decreased expression in the obese population; three genes, including XLOC_004699, COX6B2 and RXFP2, had increased expression in the obese population. The results of existing studies showed that COX6B2 was closely associated with pancreatic cancer development and metastasis, and was con rmed to be differentially expressed between groups in a study of colonic gene expression in obese rats in which axseed polysaccharide altered lipid metabolism and energy metabolism, indicating that it may have a role in affecting lipid metabolism [21]. The main functional enrichments involved in differentially expressed genes include PEROXISOME, BILE_ACID_METABOLISM, OXIDATIVE_PHOSPHORYLATION, and FATTY_ACID_METABOLISM.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that eight genes, including XLOC_003676, XLOC_011515, VAX1, Q07610, RIMBP2, OR5T1, XLOC_013038 and PTPN3, had decreased expression in the obese population; three genes, including XLOC_004699, COX6B2 and RXFP2, had increased expression in the obese population. The results of existing studies showed that COX6B2 was closely associated with pancreatic cancer development and metastasis, and was con rmed to be differentially expressed between groups in a study of colonic gene expression in obese rats in which axseed polysaccharide altered lipid metabolism and energy metabolism, indicating that it may have a role in affecting lipid metabolism [21]. The main functional enrichments involved in differentially expressed genes include PEROXISOME, BILE_ACID_METABOLISM, OXIDATIVE_PHOSPHORYLATION, and FATTY_ACID_METABOLISM.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research indicates that plant polysaccharides exhibit multi-target and multi-pathway characteristics [ 45 ]. Given the close association of polysaccharides with the energy metabolism of organisms [ 46 , 47 ], we developed a chronic inflammatory injury cell model using C28 chondrocytes TNFα induction, subsequently intervening with SP for a duration of 10 days. To explore the potential mechanisms, we investigated cellular biological processes through RNA-seq analysis.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that FUNDC1- and ACSL4-dependent ferroptosis may serve as a target for early obesity-induced cardiac dysfunction. In addition, a transcriptomic study of flaxseed polysaccharide (FP)-treated rats also suggests an important role for ACSL4 in the development of obesity [ 138 ].…”
Section: Acsl4 In Diseasesmentioning
confidence: 99%